Protonic conductivity and viscoelastic behaviour of Nafion (R) membranes with periodic mesoporous organosilica fillers - Rosero-Navarro, Nataly C.
Benzene-bridged periodic mesoporous organosilicas functionalised with sulfonic acid (SPh-PMO) are explored as fillers to improve the protonic conductivity and the viscoelastic properties of Nafion (R). Homogeneous membranes with 5, 10 and 20 wt.% submicrometric SPh-PMO particles (roughly corresponding to 11, 20 and 36 vol.%) were obtained by control of the casting suspensions. The three composite membranes have acid loads and water uptake values similar to Nafion (R). The storage modulus of the 20 wt.% S-Ph-PMO composite (0.2 GPa at 100 degrees C and 0.05 GPa at 140 degrees C) is 2.5-15 times higher than for pure Nafion (R) (respectively 0.08 and 0.005 GPa), denoting a positive effect of the fillers on the mechanical resistance of the membranes, also observed for lower filler fractions. The protonic conductivity of the composite membranes at 20% relative humidity (RH) and 40 degrees C is up to 1.5 orders of magnitude higher than for Nafion (R). The magnitude of the effect decreases with increasing humidity, with the best composite attaining 0.03 S cm(-1) at 120 degrees C/40% RH, 3 times more than Nafion (R). All membranes have similar behaviour at 98% RH, showing a maximum of 0.2 S cm(-1) at 94 degrees C, with the composites still showing slightly better performance. The results are discussed in terms of the effect of the fillers on reducing the internal swelling pressure and the activation energy for proton migration. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.